Work Spirit and Implementation of Nursing Care at the Kolaka General Hospital, Southeast Sulawesi - Zulaeni Esita (Psikologia : Jurnal Psikologi, 2015)
The implementation of nursing care that has not been done optimally, it has became a common problem in the most of government hospitals in Indonesia. Many customers feel not dissatisfied for health care services received from government hospitals. Work motivation is considered as one of the factors that influence the implementation of nursing care in hospital. It is can provide quality health services in hospital which expected by customers. The focus of this study was about how influence of Work motivation to the implementation of nursing care, especially in the Rumah Sakit Umum (RSU)Kolaka in Southeast Sulawesi. The study was designed as a quantitative. The population in this study were all nurses who worked at the RSU Kolaka. All the population in this study were the civil servants (PNS).The sampling technique used was purposive random sampling, so that the sample used in this research consisted of 53 nurses. Analysis of the data used was a simple linear regression analysis. The results of study showed thatthe work motivation contributed 15.6%to the implementation of nursing care (R2 = 0.156) in the RSU Kolaka Southeast Sulawesi.